Development of 3D in vitro platform technology to engineer mesenchymal stem cells - Hosseinkhani H (Dove Medical Press, 2012)
Hossein Hosseinkhani,1 Po-Da Hong,1 Dah-Shyong Yu,2 Yi-Ru Chen,3 Diana Ickowicz,4 Ira-Yudovin Farber,4 Abraham J Domb41Graduate Institute of Biomedical Engineering, National Taiwan University of Science and Technology (TAIWANTECH), 2Nanomedicine Research Center, National Defense Medical Center, Taipei, Taiwan, 3Department of Biomedical Engineering, National Yang-Ming University, Taipei, Taiwan, 4Institute of Drug Research, The Center for Nanoscience and Nanotechnology, School of Pharmacy-Faculty of Medicine, The Hebrew University of Jerusalem, Jerusalem, IsraelAbstract: This study aims to develop a three-dimensional in vitro culture system to genetically engineer mesenchymal stem cells (MSC) to express bone morphogenic protein-2. We employed nanofabrication technologies borrowed from the spinning industry, such as electrospinning, to mass-produce identical building blocks in a variety of shapes and sizes to fabricate electrospun nanofiber sheets comprised of composites of poly (glycolic acid) and collagen. Homogenous nanoparticles of cationic biodegradable natural polymer were formed by simple mixing of an aqueous solution of plasmid DNA encoded bone morphogenic protein-2 with the same volume of cationic polysaccharide, dextran-spermine. Rat bone marrow MSC were cultured on electrospun nanofiber sheets comprised of composites of poly (glycolic acid) and collagen prior to the incorporation of the nanoparticles into the nanofiber sheets. Bone morphogenic protein-2 was significantly detected in MSC cultured on nanofiber sheets incorporated with nanoparticles after 2 days compared with MSC cultured on nanofiber sheets incorporated with naked plasmid DNA. We conclude that the incorporation of nanoparticles into nanofiber sheets is a very promising strategy to genetically engineer MSC and can be used for further applications in regenerative medicine therapy.Keywords: 3D culture, nanoparticles, nanofibers, polycations, tissue engineering